The Effectiveness of STEM Inquiry-Based E-Book on Temperature and Heat to Improve Senior High School Students’ Scientific Literacy - Nola Afri Jolida; Dadan Rosana (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
Education in Indonesia faces low student abilities in scientific literacy. Scientific literacy is essential for students to understand, evaluate, and use knowledge so they can use scientific concepts in learning and daily life. This study aims to determine the effectiveness of STEM inquiry-based e-books on temperature and heat in improving high school students' scientific literacy skills. This study uses a quasi-experimental research design and cluster random sampling technique. Data analysis used statistical tests using the SPSS application. Prerequisite tests were carried out in stages, namely normality tests and homogeneity tests. Effectiveness tests include the N-gain test, Manova test, and Effect Size. The results of this study indicate that the use of STEM inquiry-based e-books on temperature and heat is better in improving students' scientific literacy skills. The effectiveness of STEM inquiry-based e-books on temperature and heat is obtained based on the difference in average pretest-posttest scores and the increase in pretest-posttest scores in each class. The experimental class that used STEM inquiry-based e-book learning products on temperature and heat material experienced higher improvement compared to the control class 1 that used regular e-books without inquiry models and the control class 2 that used printed school books.